GAMBARAN SUBJECTIVE WELL-BEING PADA SISWA PASCA TOXIC RELATIONSHIP DI SMA BATIK1 SURAKARTA - Hermawan, Galuh Hermawan; Faqih Purnomosidi; Sri Ernawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the subjective well-being (SWB) of students who have experienced toxic relationships. A qualitative approach with a descriptive phenomenological method was used to explore the subjective experiences of six informants consisting of three main informants and three supporting informants. Data were collected through in-depth interviews and non-participant observation. The results showed that after leaving toxic relationships, students experienced increased positive affect, such as feelings of relief, happiness, and self-confidence, healthier cognitive evaluations of life, as well as improved social relationships and spirituality. Social support from friends and family, along with involvement in spiritual activities such as worship, also strengthened the recovery process of subjective well-being. These findings indicate that the integration of affect, cognitive evaluation, social relationships, and spirituality forms an important foundation in the recovery and strengthening of students’ psychological well-being after unhealthy relationships.